Sensory, chemical and consumer analysis of Brettanomyces spoilage in South African wines - Botha, Janita J (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc Food Sc (Food Science))--University of Stellenbosch, 2010.